Development of service infrastructure for private motor boats in the northern regions - Shvetsova Svetlana (E3S Web of Conferences, 2024)
This article examines the current trends in the development of infrastructure for the maintenance and repair of private motor boats in the northern regions (on the example of the Republic of Sakha (Yakutia)). A survey of motor boat owners in three different groups was conducted. The survey data provide data on the most relevant areas of infrastructure development for the maintenance and repair of private motor boats in the region. Results of the study of current trends in the development of infrastructure for maintenance and Repair of private motor boats can be used for the development of programs for the development of water transport infrastructure, by manufacturers of motor boats, as well as in conducting new research in this area.